2016
DOI: 10.7763/ijesd.2016.v7.746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Regimes and Organic Matter Strategies on Mitigating Green House Gas Emission from Rice Cultivation and Co-benefits in Agriculture in Vietnam

Abstract: Abstract-Agriculture sector in Vietnam is not only affected by climate change but it also emits a high proportion of greenhouse gas (GHG) -especially rice, which is the main source of GHG emissions in this sector. Many GHG mitigation options have been transferred to rice cultivation in the world with biochar measure, compost measure and applying Alternative Wet and Dry (AWD) measures having high potential to reducing GHG emissions. This study assesses the co-benefits of greenhouse gas emission mitigation optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Emissions of CH 4 from rice production are recognised as a significant source of GHG emissions globally, and many studies show that changes in water management can substantially reduce CH 4 emissions ( Liu et al, 2010 , Nayak et al, 2015 , Yan et al, 2005 ). It is possible to reduce CH 4 emissions and increase yield through optimising drainage and manure management ( Banerjee et al, 2002 , Malla et al, 2005 , Thu et al, 2016 ). Specifically, changing a continuously-flooded system to intermittent irrigation shows potential to greatly reduce CH 4 emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Emissions of CH 4 from rice production are recognised as a significant source of GHG emissions globally, and many studies show that changes in water management can substantially reduce CH 4 emissions ( Liu et al, 2010 , Nayak et al, 2015 , Yan et al, 2005 ). It is possible to reduce CH 4 emissions and increase yield through optimising drainage and manure management ( Banerjee et al, 2002 , Malla et al, 2005 , Thu et al, 2016 ). Specifically, changing a continuously-flooded system to intermittent irrigation shows potential to greatly reduce CH 4 emissions.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one published study available on methane emissions in the MRD, but that focuses on straw burning and mushroom production (Arai et al 2015), so the reported values cannot be taken as a reference for our study. Moreover, there are few studies from other deltas of Vietnam available such as the Red River Delta in North Vietnam (Pandey Nguyen et al 2014;Nguyen et al 2016;Vu et al 2015;Tariq et al 2017) and the Vu Gia/Thu Bon delta in Central Vietnam (Tirol-Padre et al 2017) which reported values ranging from 104 to 696 kg CH 4 ha −1 per season. Although these data sets will not be directly applicable to the MRD because the hydrological conditions are very distinct in the different deltas of Vietnam, most of the seasonal emissions we obtained from the MRD are within the range that has been reported in North and Central Vietnam except for some very low emissions in the saline soils and the very high in the deep flood zone.…”
Section: Zonal Differentiation and Seasonal Patternsmentioning
confidence: 99%
“…The deltaic rice production systems are characterized by very specific hydrological conditions as compared to other rice-growing environments (Wassmann et al 2009), so that the application of default emission factors may be erroneous. However, there are only few studies published on methane emissions of rice grown in such environments (Pandey Nguyen et al 2014;Arai et al 2015;Vu et al 2015;Nguyen et al 2016;Tariq et al 2017;Tirol-Padre et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…,Akiyama et al (2010) Barcon et al (2015),Basak (2015),Bates et al (2009),Bell et al (2010),Bylin et al (2010),Dickie et al (2014),Eagle et al (2012), EC (2015),Eom et al (2016),Eory et al (2016),Feng et al (2013),Frutos et al (2017),Han et al (2010),Harnisch et al (2006), Henderson et al (2015), Hinde et al (2016), Hristov et al (2013), Hui et al (2010), Hulshof et al (2012), IPCC/ TEAP (2005), Jiao et al (2006), Karakurt et al (2012), Kinley et al (2016), Launio et al (2016), Lebrero et al (2016), Lechtenböhmer and Dienst (2010), Li et al (2014), Linquist et al (2012), Lipsky (2014), Lopez et al (2013), MacLeod et al (2010), McKinsey (2010), Moran et al (2008), Nalley et al (2015), Nayak et al(2015),Ndegwa et al (2008),Nunotani et al (2016),Park et al (2008),Patel et al (2016),Petersen et al (2012),Ravikumar and Brandt (2017),Reid et al (2014),Smith et al (2008),Sun et al (2017),Tariq et al (2017),Thu et al (2016),Torralbo et al (2017),Towprayoon et al (2005),Tyagi et al (2010), Van Zijderveld et al(2011),Wassman et al (2000),Weiske and Michel (2007),Wu et al (2017),Yang et al (2012),Yu et al (2004),Yue et al (2005),Yusuf et al (2012),Zhang et al (2016) andZhu et al (2016). (continued on next page)…”
mentioning
confidence: 99%